2023
DOI: 10.3389/fnut.2023.1048230
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting and immunomodulatory effects: A systematic review

Abstract: Introductionstrategy of periodic food restriction and fixed eating windows, could beneficially modify individuals by losing body weight, regulating glucose or lipid metabolism, reducing blood pressure, and modulating the immune system. Specific effects of IF and its mechanisms have not yet been assessed collectively. Thus, this systematic review aims to summarize and compare clinical trials that explored the immunomodulatory effects of IF.MethodsAfter screening, 28 studies were included in this systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, we observed a reduction in MDA levels in the IF + CD and IF + KD groups, indicating that IF might mitigate KD-induced oxidative stress. Tis aligns with the fndings of He et al [40], who reported that IF could attenuate oxidative stress and improve antioxidant defense mechanisms. Furthermore, the changes in GSH levels and catalase activity observed in our study support the potential protective role of IF against oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, we observed a reduction in MDA levels in the IF + CD and IF + KD groups, indicating that IF might mitigate KD-induced oxidative stress. Tis aligns with the fndings of He et al [40], who reported that IF could attenuate oxidative stress and improve antioxidant defense mechanisms. Furthermore, the changes in GSH levels and catalase activity observed in our study support the potential protective role of IF against oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…A total of 12,815 participants were eligible for inclusion and therefore incorporated into the analyses (Figure 1). function dysfunction, and energy metabolism disorders are key in the pathogenesis of obesity [8,[23][24][25]. Thus, it is hypothesized that Se may influence obesity levels.…”
Section: Study Populationmentioning
confidence: 99%
“…Selenium (Se), an essential trace element and constituent of selenoproteins, plays many vital physiological roles, including antioxidation, anti-inflammation, anti-aging, energy metabolism, immune regulation, redox signaling, cellular differentiation, protein folding, and gene expression [13][14][15][16][17][18][19][20][21][22]. Oxidative stress (OS), inflammation, endocrine function dysfunction, and energy metabolism disorders are key in the pathogenesis of obesity [8,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…TRE/IF has a profound effect on promoting immune system homeostasis [113]. Fasting improves mitochondrial health [114][115][116][117] and protects hematopoietic stem cells from damage [118].…”
Section: Fasting and Autophagymentioning
confidence: 99%